2004
DOI: 10.1007/s10397-004-0016-1
|View full text |Cite
|
Sign up to set email alerts
|

Do we really need to hysteroscope all the women who have irregular bleeding on hormone replacement therapy?

Abstract: Objective: To find out the importance of hysteroscopy in patients with irregular bleeding on HRT. Methods: Retrospective case note analysis of women attending outpatient hysteroscopy clinic between 1 August 2000 and 31 July 2001. Results: A total of 352 patients were referred to hysteroscopy clinic at Castle Hill Hospital, UK. The mean age of the patients was 57 years (range 48-69 years). The mean duration of HRT usage was 3.5 years (range 2-10 years). Seventy-seven (22%) patients had irregular bleeding on HRT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
3
1
Order By: Relevance
“…The mean age from our study was 56 years, slightly higher than the 54 years reported by Hickey et al [10]; however, it was less than 57 years of presentation reported by Lalchandani et al [9] which is likely because the average age of menopause in the United Kingdom is 51 years. However, it ranges from 45 to 55 years [11].…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…The mean age from our study was 56 years, slightly higher than the 54 years reported by Hickey et al [10]; however, it was less than 57 years of presentation reported by Lalchandani et al [9] which is likely because the average age of menopause in the United Kingdom is 51 years. However, it ranges from 45 to 55 years [11].…”
Section: Discussioncontrasting
confidence: 69%
“…The One-stop PMB clinic (also called rapid access clinic) was designed to bridge the delays associated with the outpatient assessment of women with PMB and subsequent inpatient endometrial assessment with Hysteroscopy, and populating the clinic with inappropriate referrals defeats the essential purpose of the clinic [8]. The mean duration of HRT use among the study population was 16 months, almost half the mean reported by Hickey et al [10] and significantly less than the 39 months reported in the series by Lanchadnia et al [9].…”
Section: Volume 5 -Issue 2 Int Gyn and Women's Healthmentioning
confidence: 91%
See 1 more Smart Citation
“…However, despite these developments, it is still not possible to visualize some problems with confidence, such as intrauterine adhesions [ 5 ]. Differentiating submucous fibroids from endometrial polyps can be difficult sometimes [ 6 , 7 ]. Another example is distinguishing submucous fibroids which distort the cavity from those not distorting the cavity [ 8 ].…”
Section: Introductionmentioning
confidence: 99%